Recent tectonics of the West (Sub-Dobrogea) segment of the Scythian plate and adjacent areas - V. G. Verkhovtsev (Геофизический журнал, 2010)
The results of medium-scale (1: 500 000) mapping of the recent tectonics of the region obtained on the basis of morphographic, morphometric and remote sensing investigation methods are considered. The linear and annular structures, active at the recent stage are recognized and analyzed as well as the total amplitudes of vertical Late Pliocene-Quaternary movements of the earth's crust. Reconnaissance perspectives have been evaluated on the basis of neotectonic criteria.